Physical and mechanical properties of materials prepared using Class C fly ash and soybean oil - Balo, Figen; Yucel, H. Luetfi; Ucar, Aynur (Springer, 2010)
In present work; epoxidized soybean oil (ESO), fly ash (FA) and natural clay (C) are used to produce 45 kinds of biocomposite materials and by analyzing the physical-mechanical properties of these novel materials, their use as an insulation material is investigated. The compressive strength, tensile strength, abrasion loss, thermal conductivity and oven-dry mass of each sample are measured. The minimum thermal conductivity of 0.273 W/mK is observed with the samples containing ESO-FA-C. It is increased with the decrease of ESO and FA. The compressive and tensile strengths are varied from 13.53 to 6.31 MPa and 1.287 to 0.879 MPa, respectively.
Keywords: Thermal analysis; Mechanical properties; Organic materials; Composite